Atividade física e comportamento sedentário associados aos marcadores antropométricos, inflamatórios e cardiometabólicos em adolescentes das escolas públicas de São Luís -MA - MELO, Raimunda Suely Batista (2019)
Physical activity has been recommended as it has beneficial health effects. The sedentary behavior present in the routine of adolescents, over a long period of time, has had adverse health effects, due to its association with anthropometric, inflammatory and cardiometabolic markers. The objective of this study was to analyze physical activity and sedentary behavior associated with anthropometric, inflammatory and cardiometabolic markers in adolescents from São Luís- MA, Brazil. A cross-sectional observational study was conducted from 2014-2016 with a random sample of 405 adolescents aged 17 to 18 years from the public high school in São Luís, Maranhão-Brazil. Data were collected through a validated questionnaire with socioeconomic information of the mother and adolescent, the usual physical activity (commuting, domestic and occupational tasks and physical exercise), sitting and screen time (watching television, playing video games, using the computer), on weekdays and on weekends, and as an objective measure of physical activity, the pedometer to record the number of steps / day of adolescents. Biological material was collected for the measurement of inflammatory interleukins (1β, 6 and 8) and triglyceride and HDL levels; and anthropometric or adiposity markers were measured: body mass index (BMI), waist circumference (WC), fat mass (FM). Waist / height ratio and triglyceride / HDL ratio were calculated, and the adolescents' blood pressure was measured. Data were analyzed using Structural Equation Modeling (SEM), constructed with latent variables (socioeconomic status, physical activity, sedentary behavior, adiposity and blood pressure). Exploratory factor analysis (EFA) of latent variables was performed to obtain convergent and significant factor loadings, and validated by confirmatory factor analysis (CFA). Finally, the model presented a good adjust. This thesis originated two articles: article 01, entitled “Association of Physical Activity with Inflammatory Interleukins (IL) 1β, 6, 8 in adolescents from a city of northeastern Brazil”. The latent variable physical activity had a positive association with the latent variable of inflammatory interleukins, “Inflammatory load” (CP=0,442; p<0,001) and negative with blood pressure (CP= -0,146; p=0,029). Body Mass Index (BMI) was associated with inflammatory interleukins, “Inflammatory load” (CP=0,145; p=0,025) and with blood pressure (CP=0,177; p<0,001). Females presented higher “inflammatory load” than males (CP=0,282; p<0,001). Article 2 was entitled: Are sedentary behavior and cardiometabolic risk factors in adolescents associated? The latent variable of socioeconomic status (SES) was associated with sedentary behavior (CP=0,219; p<0,0001) and anthropometric or adiposity markers (CP=0,177; p<0,0001). Sedentary behavior was not associated with adiposity, blood pressure and triglyceride / HDL ratio (cardiometabolic risk factors). The latent variable, adiposity represented by fat mass (FM), BMI and waist circumference (WC) had an association with blood pressure (CP=0,178; p=0,007), and with the triglyceride / HDL ratio (CP=0,285; p<0,0001). High levels of inflammatory activity-induced interleukins are involved in the production of anti-inflammatory cytokines, which promotes health benefits. Sedentary behavior was not associated with adiposity, blood pressure and triglyceride / HDL ratio. Physical activity that has energy expenditure is beneficial to the health of adolescents by promoting the production of anti-inflammatory cytokines; accumulated sedentary behavior over time is associated with the development of chronic diseases. It is recommended that public health policies prioritize the implementation of preventive measures against noncommunicable chronic diseases (NCCDs), determined by the WHO, such as minimizing sedentary behavior time, increasing physical activity time and adopting healthy eating habits.